PENGARUH MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPA KELAS IV SDN 16 PONTIANAK TIMUR - Suci Lestari; Rosnita Rosnita; Endang Uliyanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract This study aims to analyze how much influence from the use of project based learning model to the increase of natural science of natural outcomomes of fourth graders of public elementary school 16 pontianak east. The population in this study were all the fourth graders of the state elementary school 16 pontianak east consisting of two classes IVa and IVb. Samle of research that is 30 control class student and 34 student of experiment class of much 64 student. Result of data analysis, obtained by mean of result of student learinng control class equal to 75,47. The ruslt oh hypothesis ( t- test) separated varians. Data collection techniques used in this study is a measurement technique, the instrument used is a form of test in the form of multiple choice with the amount of 50 questions. The result of t- test got thitung 2,1303  amounted to 1,6693 and ttabel (α = 5% with dk = 38) that is meant thitung (4,2391) > ttabel (1,6693), so Ha is received. So, it can be concluded that there is effect procect based learning model of learning result of Natural Science Students class IV SDN 16 Pontianak east. The counting of effect size (ES), got ES amounted is 0,98 (high category). Keywords: model of project based learning, learning outcomes natural science